Impact of a short-term training in emergency and trauma in a tertiary teaching institute - ., Rudramani; Kumar, Vineet; Thakur, Neha; Singh, Vikas; Shakya, Shobhit; Singh, Neetu; Nath, Soumya S.; Choudhary, Richa; Chandra, Anamika; Lumbani, Amrita (International Surgery Journal, 2021)
Background: The health-workers working in emergency area need better training to handle emergency patients with sincerity and accurate clinical skills. So, it is imperative to train them on simulation models and prepare them to perform their duties with better skills and higher confidence. Methods: A structured course named as Dr. RMLIMS Emergency and Trauma-Basic Course (DrRMLIMS ET-BC), was designed to effectively train the resident doctors from different departments, nursing staff (pool A) and other health-workers, ancillary staff and security persons (pool B) posted in the casualty and emergency wards. Pool A underwent pretest to ascertain basic knowledge. Post-test questionnaire was taken after training. Predesigned google forms were used for feedback. Pool B underwent counselling and motivating sessions about the sense of team, role of leader and effective communication. Direct observation, officer in-charge’s feedback, buddy feedbacks, patient’s attendants’ feedbacks and self-appraisal were done for evaluation. Paired t test was applied on pool A pretest and post-test scores to evaluate the change in the knowledge. Results: Pool A shows a pre-test mean of 37.83±0.92 (approximately 39%) which improved significantly to 72.16±0.90 post training (p value=0.0000). Pool B revealed significant positive change in the attitude, behavior and sense of team and responsibility. Conclusions: This study shows that this training is an adequate training programme to teach the basics emergency and trauma skills and been successful in increasing knowledge, despite the variations in the vision of different subject specialities.